1868-69 N.C. Sess. Laws 59-60 - (:unkn) unknown (My University, 1868)
Pub. Laws, ch. 18, § 1: [I]f any person or persons whomsoever shall be known to hunt in this state on the Sabbath with a dog or dogs, or shall be found off of their premises on the Sabbath, having with him or them a shot-gun, rifle or pistol, he or they shall be subject to indictment; and, upon conviction, shall pay a fine not to exceed fifty dollars at the discretion of the Court, two-thirds of such fine to enure to the benefit of the free public schools in the County of which such convict is a resident, the remainder to the informant.
Keywords: CARRY; HUNTING REGULATION